Repeated measurements of the anterior segment during accommodation using long scan depth optical coherence tomography - Yuan, Yimin (2012)
OBJECTIVES: To determine the repeatability of ultra-long scan depth spectral domain optical coherence tomography (SD-OCT) measurements of the ocular anterior segment during accommodation. METHODS: The center wavelength of the SD-OCT light source was 840 nm with a bandwidth of 50 nm. The ocular axial resolution of the system was ~6.0 μm, and the scan depth was 7.2 mm in air. Twenty eyes of twenty healthy subjects were imaged with a custom-built, ultra-long scan depth SD-OCT during two visits. The anterior segment images were acquired during non-accommodative and maximal accommodative states. After image processing and correction, the true values of the morphometric dimensions of the anterior eye were obtained. The variables of the two states from two visits were compared. RESULTS: For the corrected anterior segment images, the variables did not significantly differ from one visit to the next. The values of anterior chamber depth, pupil diameter, and the radius of the lens anterior surface curvature during accommodation were significantly smaller than those during the non-accommodative state. The lens thickness significantly increased with accommodation. There was no significant difference in the posterior surface curvature of the lens between the two states. CONCLUSIONS: Ultra-long scan depth SD-OCT holds promise for quantifying dimensional changes in the eye during accommodation. The instrument demonstrated good repeatability of ocular anterior segment dimensional measurements during accommodation.